Biliary Tract Cancer: Current Roles of Radiation Therapy - Cuneo, Kyle C.; Crysler, Oxana V.; Enzler, Thomas (Digestive Disease Interventions, 2025)
Biliary tract cancers, encompassing gallbladder cancer, intrahepatic cholangiocarcinoma (IHCC), and extrahepatic cholangiocarcinoma (EHCC), are rare malignancies with limited prospective studies guiding their management. Radiation therapy has evolved significantly over the years, advancing from conventional fractionated approaches to innovative modalities such as stereotactic body radiation therapy (SBRT) and hypofractionated radiation therapy. This review explores the role of radiation therapy in biliary tract cancers, with a particular focus on IHCC and EHCC, highlighting its historical evolution, current applications, and future directions. For IHCC, external beam radiation therapy has demonstrated benefits in retrospective analyses, with modern conformal techniques such as intensity-modulated radiation therapy and volumetric modulated arc therapy enabling safe dose escalation and improved local control. SBRT and hypofractionated radiation therapy offer promising alternatives for unresectable or recurrent IHCC, with high local control rates and manageable toxicity profiles reported in retrospective and early-phase prospective studies. Despite these advancements, the need for robust phase III comparative trials remains critical. In EHCC, radiation therapy plays a pivotal role in adjuvant and definitive settings. Additionally, radiation therapy is increasingly utilized as part of neoadjuvant protocols for liver transplantation candidates with unresectable hilar cholangiocarcinoma, improving outcomes when combined with strict selection criteria and modern systemic therapies. This review underscores the importance of a multidisciplinary approach to the management of biliary tract cancers, integrating radiation therapy advancements with systemic and surgical therapies. Future research should focus on personalized treatment strategies, leveraging novel technologies and biomarker-driven approaches to optimize outcomes for this challenging patient population.
Keywords: cholangiocarcinoma; radiation therapy; stereotactic body radiation therapy; biliary tract cancer